Outlaw heroes in myth and history - Seal, Graham, 1950- (London : Anthem Press, 2011)
This book provides an overview and analysis of the global tradition of the outlaw hero. The mythology and history of the outlaw hero is traced from the Roman Empire to the present, showing how both real and mythic figures have influenced social, political, economic and cultural outcomes in many times and places.
pt. 1. Myths and histories -- pt. 2. Politics and identities -- pt. 3. Legends and commodities -- pt. 4. The global outlaw.
Title from publisher's bibliographic system (viewed on 02 Oct 2015).
Keywords: Outlaws -- History; Heroes -- History